Decomposition Formulas of Kampé de Fériets Double Hypergeometric Functions (Analysis in Theory and Applications, 2018)
This paper is sequel to the authors paper [18]. By using the generalizedBurchnall-Chaundy operator method, the authors are aiming at deriving certain decompositionformulas for some interesting special cases of Kamp\u00e9 de F\u00e9riets series of double hypergeometric series $F^{p:q;k}_{l:m;n}$.
Keywords: Generalized hypergeometric function; Kampé de Fériets functions; decomposition formulas; inverse pairs of symbolic operators.